Low-Load Resistance Training With Blood Flow Restriction Improves Clinical Outcomes in Musculoskeletal Rehabilitation: A Single-Blind Randomized Controlled Trial - Ladlow, Peter; Coppack, Russell J.; Dharm-Datta, Shreshth; Conway, Dean; Sellon, Edward; Patterson, Stephen D.; Bennett, Alexander N. (Frontiers in Physiology, 2018)
Background: There is growing evidence to support the use of low-load blood flow restriction (LL-BFR) exercise in musculoskeletal rehabilitation. Purpose: The purpose of this study was to evaluate the efficacy and feasibility of low-load blood flow restricted (LL-BFR) training versus conventional high mechanical load resistance training (RT) on the clinical outcomes of patient’s undergoing inpatient multidisciplinary team (MDT) rehabilitation. Study design: A single-blind randomized controlled study. Methods: Twenty-eight lower-limb injured adults completed a 3-week intensive MDT rehabilitation program. Participants were randomly allocated into a conventional RT (3-days/week) or twice-daily LL-BFR training group. Outcome measurements were taken at baseline and 3-weeks and included quadriceps and total thigh muscle cross-sectional area (CSA) and volume, muscle strength [five repetition maximum (RM) leg press and knee extension test, isometric hip extension], pain and physical function measures (Y-balance test, multistage locomotion test—MSLT). Results: A two-way repeated measures analysis of variance revealed no significant differences between groups for any outcome measure post-intervention (p > 0.05). Both groups showed significant improvements in mean scores for muscle CSA/volume, 5-RM leg press, and 5-RM knee extension (p < 0.01) after treatment. LL-BFR group participants also demonstrated significant improvements in MSLT and Y-balance scores (p < 0.01). The Pain scores during training reduced significantly over time in the LL-BFR group (p = 0.024), with no adverse events reported during the study. Conclusion: Comparable improvements in muscle strength and hypertrophy were shown in LL-BFR and conventional training groups following in-patient rehabilitation. The LL-BFR group also achieved significant improvements in functional capacity. LL-BFR training is a rehabilitation tool that has the potential to induce positive adaptations in the absence of high mechanical loads and therefore could be considered a treatment option for patients suffering significant functional deficits for whom conventional loaded RT is contraindicated. Trial Registration: ISRCTN Reference: ISRCTN63585315, dated 25 April 2017.